The European Diploma in Musculoskeletal Radiology; Past, Present, and Future - Adriaensen, Miraude; Rupreht, Mitja; Martinoli, Carlo; Vanhoenacker, Filip; Robinson, Philip; Drakonaki, Elena (Seminars in Musculoskeletal Radiology, 2024)
As per recommendations from the European Society of Radiology and the European Union of Medical Specialists, upon completion of level 3 radiology training, an objective assessment of the attained standards, aligned with national customs and practices, should take place. A subspecialty exam should ideally be an integral part of the training completion process. Among 10 of 13 European subspecialty societies currently offering a European subspecialty diploma, the European Society of Musculoskeletal Radiology (ESSR) diploma program was formally introduced by the ESSR in 2003. This article describes the evolution of the ESSR diploma, encompassing the current diploma program, validation procedures, endorsements, and future perspectives. Additionally, insights from a brief survey among ESSR diploma holders is shared, offering valuable tips for prospective candidates aiming to navigate the examination process successfully.
Keywords: education; subspecialization; musculoskeletal imaging; European Society of Musculoskeletal Radiology; diploma